Incomplete Cesarean Scar Rupture - F Ahmadi; S Siahbazi; F Akhbari (JRI, 2013)
Background: Uterine rupture at the site of a previous cesarean scar is an uncommon but catastrophic complication of pregnancy, which is associated with significant maternal and fetal morbidity and mortality. Case Presentation: A 30-year old woman at 24th week of gestation and complaint of pain, contractions and spotting was admitted in Royan Institute in Tehran, Iran. She had a past medical history of an EP and a cesarean section delivery, respectively 4 and 2 years before hospitalization. Herniation of an amniotic membrane into the maternal bladder was found on ultrasound examination. Conclusion: Risk factors of cesarean scar rupture should be considered in women undergoing subsequent pregnancies as they need extra care. Ultrasonography can be used to evaluate women with previous cesarean section to assess the risks of scar rupture during subsequent pregnancies.
Keywords: Caesarian section, Dehiscence, Rupture, Scar